1998
DOI: 10.1002/(sici)1097-4695(19980905)36:3<441::aid-neu11>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle activity during bird song

Abstract: The apparently continuous flow of creased from ú200 ms to on average 41 ms during bird song is in reality punctuated by brief periods of minibreaths, again for both species, but inspiratory silence during which there are short inspirations called minibreaths. To determine whether these minimuscle activity did not overlap with that of the expirabreaths are accompanied, and thus perhaps caused, tory muscles. Thus, there was no indication that the by activity in inspiratory muscles, electromyographic inspiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 35 publications
3
60
1
Order By: Relevance
“…The variation in amplitude with frequency was remarkably strong, for example, from 1.5 to 2.5 kHz the average maximum amplitude level increased by more than 15 dB. This finding corroborates earlier studies which also reported positive relationships between frequency and amplitude in other songbird species [44 -47], suggesting that proximate mechanisms, such as physical impedances [65], biophysical limitations [41] or physiological constraints [66], may limit the production of loud vocalizations at the lower end of the frequency range.…”
Section: (A) Amplitude Increases With Frequencysupporting
confidence: 89%
“…The variation in amplitude with frequency was remarkably strong, for example, from 1.5 to 2.5 kHz the average maximum amplitude level increased by more than 15 dB. This finding corroborates earlier studies which also reported positive relationships between frequency and amplitude in other songbird species [44 -47], suggesting that proximate mechanisms, such as physical impedances [65], biophysical limitations [41] or physiological constraints [66], may limit the production of loud vocalizations at the lower end of the frequency range.…”
Section: (A) Amplitude Increases With Frequencysupporting
confidence: 89%
“…4 and 6) are consistent with increased difficulty or energetic investment. Faster songs can require shorter inspirations between syllables (Calder 1970;Cooper and Goller 2006;Glaze and Troyer 2006;Hartley and Suthers 1989;Suthers and Zollinger 2004;Suthers et al 1999;Wild 1998), making them potentially more difficult to produce. Repeated syllables are produced with the shortest inter-syllable intervals in the Bengalese finch and are generally the loudest syllable in the repertoire (K. Bouchard, J. T. Sakata, and M. S. Brainard, unpublished observations), thereby making an increase in repeat number potentially more effortful.…”
Section: Discussionmentioning
confidence: 99%
“…Given this mathematical relationship, any temporal structure can be explained by any two of syllable length, gap length and song tempo. Whatever the structure of the pattern generator for song, gaps must have some form of representation in the system because they correspond to activation of motor neurons driving inspiration (Wild et al, 1998;Suthers and Margoliash, 2002;Goller and Cooper, 2004). Hahnloser et al (2002) have shown that song activity is driven by regular, clock-like bursting from HVC (RA) neurons.…”
Section: Models Of Song Productionmentioning
confidence: 99%
“…Several lines of evidence suggest that this acoustic hierarchy is embedded within the underlying representation for song. Flashes of light cause birds to interrupt their song at syllable boundaries (Cynx, 1990;Franz and Goller, 2002), and the patterns of inspiration/expiration segment the song into syllables and acoustic gaps (Wild et al, 1998;Suthers and Margoliash, 2002;Goller and Cooper, 2004). Early electrophysiological experiments suggest that this structure is reflected in the anatomical hierarchy in the forebrain, with nucleus HVC (used as a proper name) being responsible for syllable sequence and nucleus robust nucleus of the arcopallium (RA) representing individual syllables (Vu et al, 1994;Yu and Margoliash, 1996).…”
Section: Introductionmentioning
confidence: 99%